Innovative Quick Response Programs in Logistics and Supply Chain Management - Cheng, T. C. Edwin; Choi, Tsan-Ming.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
Quick Response (QR) policy is a market-driven business strategy in which supply chain members work together to react quickly to volatile market demand. Nowadays, with advances in information technologies (such as RFID and ERP systems), new challenges and opportunities arise for the application of QR. This handbook explores QR extensively with a view to discovering innovative QR measures that can help tackle the observed and emerging challenges. The book is organized into four parts, which include chapters on analytical modelling and analyses, information technologies, cases, reviews, and applications. This handbook provides new analytical and empirical results with valuable insights, which will not only help supply chain agents to better understand the latest applications of QR in business, but also help practitioners and researchers to know how to improve the effectiveness of QR using innovative methods.
The Evolution of Quick Response Programs -- Impact of Information Systems on Quick Response Programs -- Fast Fashion: Achieving Global Quick Response (GQR) in the Internationally Dispersed Clothing Industry -- Modelling and Analysis of QR Programmes -- Procurement Flexibility under Price Uncertainty -- The Value of Information in Quick Response Supply Chains: An Assortment Planning View -- Improving Revenue Management: A Real Option Approach -- Supply Chain Scheduling Under Quick Response -- Dynamic Pricing of Seasonal Product without Replenishment: A Discrete Time Analysis -- Supplier Selection in Make-to-Order Manufacturing -- Enabling Technologies for QR Programmes -- Enhancing Responsiveness for Mass Customization Strategies through the Use of Rapid Manufacturing Technologies -- Innovative Process in E-Commerce Fashion Supply Chains -- The Next Generation Demand Network in Quick Response Systems: Intelligent Products, Packet Switching and Dynamic Information -- RFID$1 (Bs Applications in Quick Response Systems -- Enterprise Resource Planning Systems for the Textiles and Clothing Industry -- Simulation-based Optimization of Inventory Model with Products Substitution -- Applications and Case Studies -- Fast Fashion: Quantifying the Benefits -- Divide and Conquer: From MTO to ATO/MTO -- Quick Response Practices in the Hong Kong Apparel Industry -- Efficient Response Systems with RFID Technology: Cases in China -- The Emergence of the Fast Fashion Business Model and Imposed Quick Response Challenges for Chinese Fabric Manufacturers -- Innovative Mass Customization in the Fashion Industry -- Improving Allocation of Inventory for Quick Response to Customer Orders: A Case Study.s
Keywords: Economics; Information Systems; Management information systems; Economics/Management Science; Production/Logistics/Supply Chain Management; Management of Computing and Information Systems; Business Information Systems